The Use of Persuasive Strategies by Rishi Sunak and Joe Biden in Addressing The COVID-19 Pandemic - Jesslyn Alvina (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study examines the persuasive strategies employed by Rishi Sunak and Joe Biden in their speeches addressing the COVID-19 pandemic, drawing on theories by Beebe and Beebe (2012, 2017). Utilizing a qualitative methodology, excerpts from their speeches were analyzed to identify specific strategies. The analysis revealed that Rishi Sunak employed inductive reasoning, deductive reasoning, causal reasoning, credible evidence, new evidence, specific evidence, evidence to tell a story, concrete examples, emotion-arousing words, and appeal to several emotions (hope, pride, and courage). While Joe Biden used inductive reasoning, deductive reasoning, causal reasoning, credible evidence, specific evidence, evidence to tell a story, concrete examples, emotion-arousing words, fear appeals, and appeal to several emotions (hope, pride, and courage). In conclusion, despite differences in age, the persuasive strategies of Rishi Sunak and Joe Biden were primarily shaped by the topic and context of their speeches.